Multiwavelength study of Cygnus A I. Precession and slow jet speeds from radio observations - Steenbrugge, K; Blundell, K (2008)
We study the jet and counterjet of the powerful classical double FRII radio galaxy Cygnus A as seen in the 5, 8 and 15-GHz radio bands using the highest spatial resolution and signal-to-noise archival data available. We demonstrate that the trace of the radio knots that delineate the jet and counterjet deviates from a straight line and that the inner parts can be satisfactorily fitted with the precession model of Hjellming and Johnston. The parameter values of the precession model fits are all plausible although the jet speed is rather low (< 0.5 c) but, on investigation, found to be consistent with a number of other independent estimates of the jet speed in Cygnus A. We compare the masses and precession periods for sources with known precession and find that for the small number of AGN with precessing jets the precession periods are significantly longer than those for microquasars.